2014
DOI: 10.6007/ijarbss/v4-i3/686
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perfectionism, Psychological Hardiness, and Job Burnout of Employees at Executive Organizations

Abstract: This study investigated the relationship between perfectionism, psychological hardiness and job burnout of employees at executive organizations in Birjand County, Iran. In terms of purpose, this study is applied, and in terms of nature, it is descriptive and co relational. The population included 5000 employees and the sample composed of 356 persons according to Cochran Formula who were classified using randomized sampling. Three modified questionnaires of perfectionism, psychological hardiness, and job burnou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In supporting this finding, according to Vegani et al ( 2020), resilience can help improve positive performance and prevent negative emotions, thoughts and behaviors, and increase life satisfaction and mental well-being in healthcare services staff and the general public (Vagni et al, 2020). This finding was consistent with the results of other studies (Azeem, 2010;Kazemi & Ziaaddini, 2014;Narimani & Abbasi, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…In supporting this finding, according to Vegani et al ( 2020), resilience can help improve positive performance and prevent negative emotions, thoughts and behaviors, and increase life satisfaction and mental well-being in healthcare services staff and the general public (Vagni et al, 2020). This finding was consistent with the results of other studies (Azeem, 2010;Kazemi & Ziaaddini, 2014;Narimani & Abbasi, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…This characteristic distinguishes them from others who may fall ill under stressful circumstances (Morelock, 1994). Thereby, individuals develop an accurate understanding of the external conditions and take suitable decisions regarding themselves (Kazemi and Ziaaddini, 2014). Hardiness refers to a specific style of an individual’s personality which includes characteristics such as commitment, control and challenge that enable them to have better control over their lives (Jalilvand et al , 2015; Jimenez et al , 2014; Gito et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, they are able to handle hardships and challenges and perceive unpleasant events as less threatening (Jalilvand et al , 2015). It has been suggested that hardiness mediates the effect of high stress levels (Azeem, 2010) and that it neutralizes the impact of stress on physical and psychological disturbances (Cerezo et al , 2015; Kazemi and Ziaaddini, 2014). Even in the Indian context, a study of IT professionals examined the inter-relationships between the constructs hardiness, self-esteem and occupational stress and found that hardiness indeed helps to cope with such stress (Subramanian and Vinothkumar, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the majority of studies has differentiated perfectionistic strivings and perfectionistic concerns when examining the relationships (e.g., Caliskan, Arikan, & Saatci, 2014;Chang, 2012;Craiovan, 2014;Fairlie & Flett, 2003;Hrabluik, Latham, & McCarthy, 2012;Kazemi & Ziaaddini, 2014;Li, Hou, Chi, Liu, & Hager, 2014;Mitchelson & Burns, 1998;Ozbilir et al, in press;Philp, Egan, & Kane, 2012;Schwenke, Ashby, & Gnilka, 2014;Stoeber & Rennert, 2008;Taris et al, 2010;Tashman, Tenenbaum, & Eklund, 2010;Van Yperen, Verbraak, & Spoor, 2011).…”
Section: Perfectionism and Burnoutmentioning
confidence: 99%
“…Mitchelson and Burns (1998) higher levels of perfectionistic concerns, but not higher levels of perfectionistic strivings than healthy controls. Finally, Kazemi and Ziaaddini (2014) examined employees working in executive organizations. Only perfectionistic concerns showed a positive correlation with overall burnout (combining exhaustion, cynicism, and inefficacy), not perfectionistic strivings.…”
Section: Perfectionism and Burnoutmentioning
confidence: 99%